The advancements in targets for ferroptosis in liver diseases - Xiang, Xiaohong; Gao, Jianbo; Su, Danyang; Shi, Doudou (Frontiers in Medicine, 2023)
Ferroptosis is a type of regulated cell death caused by iron overload and lipid peroxidation, and at its core is an imbalance of redox reactions. Recent studies showed that ferroptosis plays a dual role in liver diseases, that is, as a therapeutic target and a pathogenic factor. Therefore, herein, we summarized the role of ferroptosis in liver diseases, reviewed the available targets, such as drugs, small molecules, and nanomaterials, that act on ferroptosis in liver diseases, and discussed the current challenges and prospects.